2014
DOI: 10.1177/1759091414558417
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and Posttreatment With Edaravone Protects CA1 Hippocampus and Enhances Neurogenesis in the Subgranular Zone of Dentate Gyrus After Transient Global Cerebral Ischemia in Rats

Abstract: Edaravone is clinically used for treatment of patients with acute cerebral infarction. However, the effect of double application of edaravone on neurogenesis in the hippocampus following ischemia remains unknown. In the present study, we explored whether pre- and posttreatment of edaravone had any effect on neural stem/progenitor cells (NSPCs) in the subgranular zone of hippocampus in a rat model of transient global cerebral ischemia and elucidated the potential mechanism of its effects. Male Sprague-Dawley ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 57 publications
4
16
0
1
Order By: Relevance
“…NSCs are exquisitely sensitive to oxidative stress and related damages, which obstructs the normal cellular functions and even leads to cell apoptosis [2,44]. It is suggested that the enhancement of ROS scavenging capacity or the increase of cellular antioxidant mechanisms might facilitate not only the survival of NSCs in disease conditions, but may also regulate their fate [44][45][46]. Our experimental results provide data to support FIG.…”
Section: Figsupporting
confidence: 67%
“…NSCs are exquisitely sensitive to oxidative stress and related damages, which obstructs the normal cellular functions and even leads to cell apoptosis [2,44]. It is suggested that the enhancement of ROS scavenging capacity or the increase of cellular antioxidant mechanisms might facilitate not only the survival of NSCs in disease conditions, but may also regulate their fate [44][45][46]. Our experimental results provide data to support FIG.…”
Section: Figsupporting
confidence: 67%
“…Neural stem cells (NSCs) are multipotent cells resides in different brain regions such as sub ventricular, and sub granular zone of hippocampus (Lei et al, ), and they hold a great opportunity for the future of treatments of neurodegenerative diseases such as AD, PD, ALS, and MS (Ehnert et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Global cerebral ischemia is a clinical outcome of cardiac arrest, severe hypotension, or certain operations such as cardiopulmonary bypass and cerebral intervention, which deprive the brain of oxygen and glucose. It causes severe damage to pyramidal neurons of the CA1 region and usually results in residual neurological defi cits following a recovery from ischemia (5).…”
Section: Introductionmentioning
confidence: 99%